Arbuscular mycorrhiza in coffea arabica l.: Review and meta- analysis - Cogo, Franciane Diniz; Guimarães, Paulo Tácito Gontijo; Rojas, Enrique Pouyú; Saggin Júnior, Orivaldo José; Siqueira, Jose Oswaldo; Carneiro, Marco Aurelio Carbone (Coffee Science - ISSN 1984-3909, 2017)
Coffee, a plant of global economic importance, presents a high degree of micotrophy for nutrients absorption, especially phosphorus, whose sources are scarce, and extremely required in tropical soils. Arbuscular mycorrhizal fungi (AMF) and coffee crop (Coffea arabica) have been studied for more than three decades, and therefore, analyzing and gathering these studies in a quantitative and qualitative way by means of meta-analysis and critical review of advances and trends is of great relevance. In this review, aspects such as geographic distribution, ecology, effects on plant growth, mineral nutrition, myotrophism, and symbiotic efficiency and its applications were discussed, with special emphasis on the researches carried out in Brazil. By applying the electronic databases Cab Abstracts, Springerlink, Science Direct, Scielo, Scopus, ISI, Lilascs, Woldcat, 73 studies were analyzed, including papers, dissertations and theses. The meta-analysis showed the importance of AMF for growth, plant nutrition and grain yield. Nevertheless, a gap is still evident in the evaluation of the different management strategies adopted in coffee crop and their effects on AMF. The need to extend the research under field conditions was also detected, in order to confer the real contribution of AMF in coffee biocontrol, and their action as biofertilizers and biostimulants.